Tabel Kehidupan (Life Table) dalam Matematika Aktuaria: Tinjauan Sistematis terhadap Metodologi, Aplikasi, dan Perkembangan Terkini - Fauzi, Andri Azmul; Ridwan, Lalu Muhammad; Raming, Indriasri; Tumilaar, Rinancy (JSN : Jurnal Sains Natural, 2025)
Life tables are a fundamental tool in actuarial mathematics, providing a systematic framework for mortality analysis and survival probability calculations. This study aims to provide a comprehensive overview of life table construction methodology, its applications in the insurance and pension industries, and recent developments in this field. Using a systematic literature review approach, this study analyzes 20 relevant publications from 2014–2024, with a particular focus on the 10 most recent publications from the past 5 years. The results show that life tables have undergone significant evolution in their construction methodology, particularly with the integration of machine learning and big data analysis techniques. Applications of life tables have also expanded, encompassing not only life insurance premium calculations and actuarial valuations, but also longevity risk analysis, retirement planning, and public health policy. Recent developments indicate an increasing trend in the use of stochastic models, dynamic mortality projections, and adaptation to global demographic changes. This study contributes to a holistic understanding of the role of life tables in modern actuarial mathematics and provides insights into future development directions.